God and guns: the Bible against American gun culture - Hays, Christopher B.; Crouch, Carly L. (Presbyterian Publishing Corporation, 2021)
Using the Bible as the foundational source and guide, while also bringing contemporary sociological data to the conversation, seven biblical scholars and theologians construct a powerful dialogue about gun violence in America, concluding that guns are incompatible with the God of Christian Scripture.